On the synthesis and characterisation of novel composite-structured high-entropy alloys. (3rd August 2019) - Kumar, Anil; Parganiha, Digvijay; Verma, Jageshwar; Biswas, Prasenjit; Basu, A.; Chopkar, Manoj
ABSTRACT: A study of novel composite-structured CoCrFeNi3 Si, CoCrFe2 Ni2 Si and Co2 CrFeNi2 Si high-entropy alloys, synthesised by vacuum arc melting, is presented. The designing criteria for the formation of such alloys were based on the enthalpy of mixing and the valence electron concentration. X-ray diffraction analysis revealed that all the alloys were composed of face-centered cubic and intermetallic phases. Scanning electron microscopy, along with elemental analysis, indicated that the face-centered cubic phase mainly contains Co, Cr, Fe and Ni, whereas, the intermetallic compound is Ni-Si rich. All the synthesised high-entropy alloys in the present investigation possess excellent compressive strength along with ductility at room temperature, suggesting significant potential application in the engineering field. Furthermore, enhanced hardness, wear resistance and corrosion resistance were achieved in all the designed high-entropy alloys. The previously given design parameters for the composite-structured high-entropy alloys are in good accord with the current research work.